The validation of ocean surface heat fluxes in AMIP - Gleckler, P. J.; Randall, D. A. (Lawrence Livermore National Laboratory, 1993)
Recent intercomparisons of Atmospheric General Circulation Models (AGCMS) constrained with sea-surface temperatures have shown that while there are substantial differences among various models (with each other and available observations), overall the differences between them have been decreasing. The primary goal of AMIP is to enable a systematic intercomparison and validation of state-of-the- art AGCMs by supporting in-depth diagnosis of and interpretation of the model results. Official AMIP simulations are 10 years long, using monthly mean Sea-Surface Temperatures (SSTs) and sea ice conditions which are representative of the 1979--1988 decade. Some model properties are also dictated by the design of AMIP such as the solar constant, the atmospheric COsub 2 concentration, and the approximate horizontal resolution. In this paper, some of the preliminary results of AMIP Subproject No. 5 will be summarized. The focus will be on the intercomparison and validation of ocean surface heat fluxes of the AMIP simulations available thus far.